Comparative Analysis of Risk and Return of Sharia Stocks with Conventional Stocks - Isti’anah; Muhyarsyah (LifeSciFi, 2025)
The rapid growth of investment in the Indonesian capital market has sparked an increasing interest in both sharia-based and conventional stocks. This study aims to analyze and compare the level of risk and return rate between sharia stocks that are members of the Jakarta Islamic Index 70 (JII70) and conventional stocks in the LQ45 index in the 2019–2023 period. This study uses a quantitative approach with a comparative descriptive method. The data analysis technique was carried out using the calculation of return and standard deviation as risk indicators, as well as a difference test using an independent sample t-test to determine the significance of the difference between the two types of stocks. The results of the study show that there is a significant difference between sharia stocks and conventional stocks in terms of return and risk. In general, sharia stocks show a higher rate of return and lower risk compared to conventional stocks. These findings serve as an important reference for investors in considering investment alternatives that are not only financially competitive, but also in accordance with ethical and sustainability principles.